2012
DOI: 10.1016/j.ajhg.2012.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in COX7B Cause Microphthalmia with Linear Skin Lesions, an Unconventional Mitochondrial Disease

Abstract: Microphthalmia with linear skin lesions (MLS) is an X-linked dominant male-lethal disorder associated with mutations in holocytochrome c-type synthase (HCCS), which encodes a crucial player of the mitochondrial respiratory chain (MRC). Unlike other mitochondrial diseases, MLS is characterized by a well-recognizable neurodevelopmental phenotype. Interestingly, not all clinically diagnosed MLS cases have mutations in HCCS, thus suggesting genetic heterogeneity for this disorder. Among the possible candidates, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 38 publications
3
110
1
Order By: Relevance
“…The authors proposed that COX7B is indispensable for COX assembly, COX activity, and mitochondrial respiration (Indrieri et al, 2012).…”
Section: Subunit Viib-1mentioning
confidence: 99%
“…The authors proposed that COX7B is indispensable for COX assembly, COX activity, and mitochondrial respiration (Indrieri et al, 2012).…”
Section: Subunit Viib-1mentioning
confidence: 99%
“…2,3 To date, only three structural subunits have been associated with disease; we reported a mutation in COX4I2 in a patient with exocrine pancreatic insufficiency, 4 Indrieri et al reported an unconventional mitochondrial disease characterized by microphthalmia with linear skin lesions caused by a COX7B defect and Massa et al described a mutation in the nuclear-encoded COX6B1 in a case of infantile encephalomyopathy. 5,6 We hereby present the second reported case of mutated COX6B1 due to a novel mutation, while expanding the clinical spectrum to include cardiomyopathy, and evaluating various therapeutic small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, COX deficiency is one of the most frequent causes of mitochondrial encephalomyopathies in humans (11). Mutations in the three mtDNA-encoded COX subunits and nuclear-encoded subunits COX4, COX6b, and COX7b have been identified in patients (12)(13)(14)(15)(16)(17), although these defects are relatively rare. Most COX deficiencies described to date are caused by mutations in assembly factors (8,11).…”
mentioning
confidence: 99%